Xanthones for melanogenesis inhibition : Molecular docking and QSAR studies to understand their anti-tyrosinase activity - Rosa, Gonçalo P. (2021)
The human skin is constantly exposed to external factors that affect its integrity, UV radiation being one of the main stress factors. The repeated exposure to this radiation leads to increased production of Reactive Oxygen Species (ROS) which activate a series of processes involved in photoaging. Excessive UV exposure also exacerbates melanin production leading to a variety of pigmentation disorders. Xanthones are reported to exhibit properties that prevent deleterious effects of UV exposure and high levels of ROS in the organism, so in this work a wide library of xanthones with different patterns of substitution was synthesized and tested for their inhibitory activity against the skin enzymes tyrosinase, elastase, collagenase and hyaluronidase, many of which were evaluated for the first time. Most of the compounds were tyrosinase inhibitors, with the best one (xanthone 27) presenting an IC50 of 1.9 µM, which is approximately 6 times lower than the IC50 of the positive control kojic acid. Concerning the other enzymes, only one compound presented IC50 lower than 150 µM in elastase inhibition (xanthone 14 = 91.8 µM) and none in collagenase and hyaluronidase inhibition. A QSAR model for tyrosinase inhibitory activity was built using six molecular descriptors, with a partial negative surface area descriptor and the relative number of oxygen atoms being positively contributing to the tyrosinase inhibitory activity. Docking using AutoDock Vina shows that all the tested compounds have more affinity to mushroom tyrosinase than kojic acid. Docking results implied that the tyrosinase inhibitory mechanisms of xanthonic derivatives are attributed to an allosteric interaction. Taken together, these data suggest that xanthones might be useful scaffolds for the development of new and promising candidates for the treatment of pigmentation-related disorders and for skin whitening cosmetic products.